2018
DOI: 10.3415/vcot-16-09-0135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rotation Force to Maintain Acetabular Ventroversion after Double Pelvic Osteotomy and 2.5 Pelvic Osteotomy in a Canine Cadaveric Model

Abstract: Dorsal cortex osteotomy of the ischium decreases the acetabular segment rotation force. Decreased force may facilitate acetabular rotation during DPO procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…One of the "game changers" in the techniques used to perform pelvic osteotomies was the implementation of locking screw systems for traditional pelvic plates. Recent studies have shown a tremendous decrease in screw related complication to 0.5% (34). Locking technology reduces the need for precise plate contouring because the locking screws do not rely on friction between the plate and the underlying bone and this may significantly reduce the incidence of screw loosening.…”
Section: Complicationsmentioning
confidence: 99%
“…One of the "game changers" in the techniques used to perform pelvic osteotomies was the implementation of locking screw systems for traditional pelvic plates. Recent studies have shown a tremendous decrease in screw related complication to 0.5% (34). Locking technology reduces the need for precise plate contouring because the locking screws do not rely on friction between the plate and the underlying bone and this may significantly reduce the incidence of screw loosening.…”
Section: Complicationsmentioning
confidence: 99%